Effects of fuel component, airflow field and obstacles on explosion characteristics of hydrogen/methane mixtures fuel. (15th February 2023) - Cai, Peng; Liu, Zhenyi; Li, Pengliang; Zhao, Yao; Li, Mingzhi; Li, Ranran; Wang, Chen; Xiu, Zihao
Abstract: To popularise hydrogen/methane mixtures and determine it explosion hazards, explosion experiments were conducted based on a pipeline that can characterise urban pipe gallery scenes. The results showed that the overpressure and rate of pressure first increased and then decreased with an increase in the equivalence ratio, and increased with an increase in the hydrogen blending ratio. The heat loss and adiabatic pressure decrease with an increase in the hydrogen blending ratio, and the combined effects of the two result in different chain-based growth rates of explosion overpressure. The proportion of hydrogen blended was set to 15%. The overpressure and rate of pressure rise increased approximately linearly with the increase in airflow field intensity, and the change in the rate of pressure rise induced by airflow field was more serious than that of the overpressure. The overpressure and rate of pressure increase first increased and then decreased with an increase in the blocking ratio, and the maximum value was reached at a blocking ratio of 0.75. The explosion hazard of a low blocking ratio was less than that of a high blocking ratio. The results can provide important information for the practical use of hydrogen/methane mixtures, particularly in safety protection. Graphical abstract: Image 1 Highlights: The overpressure and the rate of pressure rise first increases and then decreases with the increase of equivalence ratio. The increased hydrogen blending ratio increases the overpressure and the rate of pressure rise. The growth of explosion characteristics is linearly related to the increase of airflow field strength. Explosion hazard of low blocking ratio is less than that of high blocking ratio.